1989
DOI: 10.1136/sti.65.5.316
|View full text |Cite
|
Sign up to set email alerts
|

Early yaws, imported in The Netherlands.

Abstract: Early yaws in a 9 year old girl from Ghana, diagnosed as imported disease in The Netherlands is reported. She had lived in The Netherlands for six months. Tropical non-venereal treponematoses are rarely seen in Europe, and only a few case reports have been published. Migration and travelling may confront the medical profession with cases of tropical diseases such as yaws. Positive serological reactions in non-venereal tropical or venereal treponematoses cannot be distinguished at present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In 1980, TPE strain CDC 2575 was isolated in Akorabo, Ghana, from a 6-year-old female patient from a papillomatous lesion and inoculated into hamsters [ 8 ], and later propagated in New Zealand White rabbits [ 9 ]. TPE strain Ghana-051 was isolated in 1988 from a papillomatous lesion of 9-year-old girl who was infected at an unspecified location in Ghana six months prior to admission to Sophia Children's Hospital in Rotterdam, The Netherlands [ 10 ]. An extract from a biopsy of this patient in secondary yaws stage was inoculated into New Zealand White rabbits in the Netherlands [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 1980, TPE strain CDC 2575 was isolated in Akorabo, Ghana, from a 6-year-old female patient from a papillomatous lesion and inoculated into hamsters [ 8 ], and later propagated in New Zealand White rabbits [ 9 ]. TPE strain Ghana-051 was isolated in 1988 from a papillomatous lesion of 9-year-old girl who was infected at an unspecified location in Ghana six months prior to admission to Sophia Children's Hospital in Rotterdam, The Netherlands [ 10 ]. An extract from a biopsy of this patient in secondary yaws stage was inoculated into New Zealand White rabbits in the Netherlands [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, exceptions to these rules occur. Several imported cases of yaws and bejel in children and adults in Europe and North America have been described [7][8][9][10]. In addition, recent studies by Noda et al [11] and Kawahata et al [12] have identified TEN in clinical samples from Cuban and Japanese patients, respectively, who had previously been diagnosed with syphilis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, yaws may mimic venereal syphilis (Wilson, 1973; Engelkens et al , 1990), or the symptoms of a previous yaws infection may mask those of a new syphilis infection (Wilson & Mauger, 1973). In addition, population data are not always readily available, as for patients who have recently immigrated (Engelkens et al , 1989), or two infections may be present in the same population (Lagarde et al , 2003). As yaws eradication efforts near their goal (Lahariya & Pradhan, 2007) and case diagnosis becomes more difficult, a molecular means of determining whether the infection is venereal or nonvenereal becomes essential.…”
Section: Introductionmentioning
confidence: 99%